New species of the genus Chydaeus from China, Nepal, Myanmar, and Thailand, with remarks on species previously described (Coleoptera: Carabidae: Harpalini) - Kataev, Boris M.; Wrase, David W.; Schmidt, Joachim (Zootaxa, 2014)
Ten new species of the genus Chydaeus Chaudoir, 1854 are described: C. dissimilis sp. n. (the bedeli species group) from the Doi Inthanon Mountain, Chiang Mai Province, Thailand; C. shaanxiensis sp. n. (the kasaharai species group) from the Daba Shan Mountain Range, southern Shaanxi, China; C. kabaki sp. n. (the kasaharai species group) from southern Sichuan, China; C. weishanensis sp. n. (the kasaharai species group) from the northern part of Wuliang Shan, western Yunnan, China; C. belousovi sp. n. (the kasaharai species group) from the south-western Yunnan, China; C. putaoensis sp. n. (the kasaharai species group) from the environments of Putao, the northernmost part of Myanmar; C. ganeshensis sp. n. (the irvinei species group) from the Ganesh Himal, Central Nepal; C. chuliensis sp. n. (the semenowi species group) from the Manaslu Himal, Central Nepal; C. wuliangensis sp. n. (the semenowi species group) from the northern part of Wuliang Shan, western Yunnan, China; C. luxiensis sp. n. (the semenowi species group) from the environments of Luxi, western Yunnan, China. New data about the distribution of the following species are provided: C. kasaharai Ito, 2002, C. shunichii Ito, 2006, C. semenowi (Tschitschérine, 1899), C. convexus Ito, 2002, C. baoshanensis Kataev & Liang, 2012, and C. obtusicollis Schauberger, 1932. The following taxa are reported for the first time: Chydaeus semenowi, C. obtusicollis and C. bedeli interjectus Kataev & Schmidt, 2002 from the Indian state Arunachal Pradesh, C. bedeli difficilis Kataev & Schmidt, 2002 from Myanmar, and C. similis Kataev & Schmidt, 2002 from the Chinese provinces Shaanxi and Chongqing.